HOW STABLE ARE INSTRUMENTAL BIASES P2-C2? - Krasuski, Kamil (Informatyka, Automatyka, Pomiary w Gospodarce i Ochronie Środowiska, 2015)
This paper presented results of investigations about estimation DCB P2-C2 for satellites and receiver in GPS system. The data from LAMA station in Poland were used to determination of stability instrumental biases P2-C2, using least square method. Author proposed new strategy to solution of DCB P2-C2 (biases were calculated with temporal resolution 2 hours). The test results were compared with CODE’s product. Difference between proposed method and CODE’s values for Satellite DCB is less than ± 1 ns and for Receiver DCB less than ± 0.2 ns. Standard deviation of presented method is about 0.4 ns.